Synthesis and Characterization of Sulfated Zirconia Catalyst for Light Naphtha Isomerization Process - Al-Tabbakh, Ban A.; Dawood, Maan M. (Journal of Petroleum Research and Studies, 2022)
The platinum-loaded zirconium oxide (Pt/SO4-2/ZrO2) catalyst was developed for the light naphtha atoms over the reaction temperature range of 160 to 220 °C, 1 and 3 h-1 LSHV and 10 bar. Platinum improved the stability of the catalyst by preventing the formation of a coke precursor at the strong acid site of sulfur zirconium. The acidity of the catalyst was characterized by of NH3-TPD and the effect of sulfur and calcination temperature on the surface area of ​​the final prepared zirconia was studied. The prepared catalyst shows high structural similar activity at temperature between 200 and 210°C for two types of light naphtha feed.